Initial dosage optimization of olanzapine in patients with bipolar disorder based on model-informed precision dosing: a study from the real world - Chen, Xiao; Hu, Ke; Shi, Hao-Zhe; Chen, Liang; Zhang, Yi-Jia; He, Su-Mei; Zhang, Cun; Wang, Dong-Dong (Frontiers in Pharmacology, 2024)
Objectives: Olanzapine is used for treating bipolar disorder (BPD), however the optimal initial dosing regimen is unclear. The present study aimed to investigate optimal olanzapine initial dosage in patients with BPD via model-informed precision dosing (MIPD) based on real world study. Methods: 39 patients with BPD from real world study were collected to construct MIPD model. Results: Weight, combined used quetiapine influenced olanzapine clearances in patients with BPD, where the clearance rates were 0.152:1 in patients with or without quetiapine under the same weight, respectively. We simulated once a day or twice a day olanzapine doses, among which twice a day was optimal. Without quetiapine, for twice a day olanzapine doses, 0.80, 0.70, 0.60 mg/kg/day were suitable for 40-56, 56-74, and 74-100 kg BPD patients, respectively. With quetiapine, for twice a day olanzapine dose, 0.05 mg/kg/day were suitable for 40-100 kg BPD patients. Conclusions: It was the first time to investigate optimal olanzapine initial dosage in patients with BPD via MIPD based on real world study, providing clinical reference for precision medication of olanzapine in BPD patients.